1997
DOI: 10.1046/j.1365-2958.1997.5001872.x
|View full text |Cite
|
Sign up to set email alerts
|

Overinitiation of chromosome replication in the Escherichia coli dnaAcos mutant depends on activation of oriC function by the dam gene product

Abstract: SummaryThe activity of DnaA protein, the initiator of chromosome replication in Escherichia coli, is regulated by adenine nucleotide binding; the ATP-bound form, not the ADP-bound form, is active. DnaAcos is a mutant protein that is insensitive to negative regulation by

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0
1

Year Published

1998
1998
2017
2017

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 21 publications
(32 citation statements)
references
References 60 publications
1
30
0
1
Order By: Relevance
“…By carrying out transposon mutagenesis of the dnaAcos mutant, which exhibits overinitiation of replication and inhibition of growth at 30 ° C (Katayama & Kornberg 1994;Katayama 2001), we previously confirmed that the dam gene, which encodes the Dam methyltransferase, is a stimulatory factor for initiation ( Katayama et al . 1997).…”
Section: Introductionmentioning
confidence: 83%
See 3 more Smart Citations
“…By carrying out transposon mutagenesis of the dnaAcos mutant, which exhibits overinitiation of replication and inhibition of growth at 30 ° C (Katayama & Kornberg 1994;Katayama 2001), we previously confirmed that the dam gene, which encodes the Dam methyltransferase, is a stimulatory factor for initiation ( Katayama et al . 1997).…”
Section: Introductionmentioning
confidence: 83%
“…To test this idea, we first quantified cellular levels of DnaA protein in wild-type and dnaA508 strains with or without hspQ::mini-kan by immunoblot analysis as previously described (Katayama & Kornberg 1994;Katayama et al 1997). The introduction of hspQ::mini-kan did not affect the level of DnaA in the wild-type dnaA strain (Table 2).…”
Section: Figurementioning
confidence: 99%
See 2 more Smart Citations
“…pTOA5 (2.7 kb) and pTOA24 (6.1 kb) minichromosomes bearing oriC-mioC and gidA-oriC-mioC regions, respectively, in addition to the ␤-lactamase gene, were kindly provided by Dr. Tohru Ogawa (32). The media used are described in a previous report (24,26,33). M9 medium was supplemented with 0.2% glucose, 2 g/ml thiamine, 20 g/ml tyrosine, and 40 g/ml each of isoleucine, valine, threonine, methionine, and tryptophan.…”
Section: Methodsmentioning
confidence: 99%